Intentional Design of Marketplace Revitalization Program: Outcome Mapping For The Case of The Banjaran Market - Chairil Zidane; Allis Nurdini (Syntax Literate, 2023)
Marketplace revitalization is a solution from the government and related stakeholders to maintain the existence of the declining traditional marketplace. One of the Indonesian marketplaces that intervened with the revitalization program for this case study is Banjaran Market, in Bandung Regency, West Java which aims to improve infrastructure performance and the socio-economic development of its surrounding community. The complexity and expected behavioral changes in the marketplace revitalization program need to be simplified to be easily understood by the implementing team, beneficiaries, and donors via Outcome Mapping analytical method. This study started by collecting qualitative data, then focusing on Step Zero and the Intentional Design stage to establish the vision, identify boundary partners, state outcome challenges, and conceptualize strategies that influence boundary partners’ behavioral changes. The results show that the Banjaran Market merchant association is the boundary partner of the revitalization program, with the expected behavioral change indicated by ‘relationship’ in the form of openness, not hindering program implementation, which in turn builds the community and business management capacity, according to the regional government and medium-term development plans. This study is accustomed to be an evaluation of other marketplace revitalization programs in Indonesia, for inclusive and sustainable community engagement and development.